Students try ways to reduce living costs - Borneo Post, (KK) (Borneo Post (kk), 2013)
SHAH ALAM: The world of cooking is only limited to the weaker sex! That was what Mohd Nashrin Abd Samad, 21, had thought since he was a small boy.